Concrescence in anterior teeth assessed by cone beam computed tomography. A case report - Aristizábal-Elejalde, David (2022)
Dental concrescence is an anomaly in which the cementum overlying the roots joins, causing the union of two different teeth. It is often reported in posterior dentition, affecting certain dental procedures such as root canal treatment, periodontal procedures, orthodontic movement, and dental extraction. This case report describes the successful diagnosis and treatment of a 20-year-old male with a moderate skeletal class II who was referred for a radiographic evaluation after 1 year of failed orthodontic movement of teeth 1.1 and 1.2. The radiographic assessment with a Cone Beam Computed Tomography allowed discarding other related pathologies and diagnosis of a dental concrescence. The patient underwent orthognathic surgery in which class II was corrected, and the concrescence was treated with a prosthetic approach.